2021
DOI: 10.3390/life11111113
|View full text |Cite
|
Sign up to set email alerts
|

Using Telemedicine to Monitor the Patient with Chronic Respiratory Failure

Abstract: Background: Advances in management have improved mortality of individuals with chronic respiratory failure (CRF), leading to an increase in need for long-term oxygen therapy and/or ventilatory support. These individuals require frequent visits and monitoring of their physiological parameters as well as of the functioning of their devices, such as ventilators or oxygen concentrators. Telemedicine is a clinical application of Information Communication Technology connecting patients to specialised care consultant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 92 publications
(116 reference statements)
0
11
0
Order By: Relevance
“…Tables 1 and 2 summarize the main results on the effectiveness of TM and tele-rehabilitation in lung diseases. However, in general, positive results are demonstrated in emergency room admissions, exacerbation-related readmissions, early detection of acute exacerbation of COPD, and health-related outcomes [25][26][27][28][29][30][31][32][33][34][35][36]. Additionally, a review of tele-rehabilitation papers showed similar, favorable outcomes compared to standard, center-based pulmonary rehabilitation in functional exercise capacity, health related quality of life, and dyspnea [37][38][39][40][41].…”
Section: Published Results On Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1 and 2 summarize the main results on the effectiveness of TM and tele-rehabilitation in lung diseases. However, in general, positive results are demonstrated in emergency room admissions, exacerbation-related readmissions, early detection of acute exacerbation of COPD, and health-related outcomes [25][26][27][28][29][30][31][32][33][34][35][36]. Additionally, a review of tele-rehabilitation papers showed similar, favorable outcomes compared to standard, center-based pulmonary rehabilitation in functional exercise capacity, health related quality of life, and dyspnea [37][38][39][40][41].…”
Section: Published Results On Effectivenessmentioning
confidence: 99%
“…Oxygen saturation measurements utility [32] Asthma Symptoms and total dose of oral prednisolone [33] Respiratory diseases Utility of noninvasive portable Digital Technologies [34] COPD Use of Forced expiratory volume assessed daily, resting respiratory rate, respiratory sounds, end-tidal carbon dioxide level [28] COPD/asthma Adherence to therapy [35] Chronic Respiratory Failure Reduction in emergency room visits, exacerbation-related readmissions, GP urgent calls, and hospitalizations [36] Table 2. Effectiveness of tele-rehabilitation in lung diseases (reviews and meta-analyses).…”
Section: Copdmentioning
confidence: 99%
“…This is true except for the most vulnerable patients, including those with tracheotomy and HIMV and their caregivers. In these categories, telemedicine may be considered to replace the usual in-person care in the referring center, depending on circumstances and patient/career preferences, with the help of structured integrated care with a multidisciplinary team of specialists and general physicians and local/home-based health care providers [ 39 , 48 ]. It is also to be considered that a diverse relationship between caregiver and patient (spouse vs. parent of the patient) may vary the approach to the problem and the related outcome.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, modalities of tele-monitoring have been proposed as a means to manage difficult-to-wean patients and VAIs 45,46 .…”
Section: Specialised Weaning Unitmentioning
confidence: 99%